Research on Sports Participation Among College Students in China: a Social-Ecological Perspective - Xiaopeng Wang; Qi Guo; Shamsulariffin Samsudin; Borhannudin Abdullah (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study aims to enhance college students' participation in sports by examining the factors influencing their engagement and exploring improvement measures across various dimensions. Utilizing the social-ecological theory, a relational model was developed to assess the impact of personal, school, and family factors on sports participation among college students. A sample of 228 students, including undergraduates, postgraduates, and PhD Candidates, was surveyed using the College Students' Sports Participation Scale. Descriptive statistics, regression analysis, confirmatory factor analysis, and structural equation modelling were conducted using SPSS 27.0 software. The multiple regression analysis results indicated that the model comprising personal, school, and family factors significantly explained 15.3% of the variance in sports participation (F (3, 227) =13.536, p=0.000). However, family factors (β=-0.09, t=-0.792, p=0.429) were not significant predictors of sports participation. In contrast, personal factors (β=0.263, t=2.513, p<0.05) and school factors (β=0.270, t=2.327, p<0.05) were significant, with school factors being the most influential predictor. The regression equation derived from the study is ŷ = 0.270x1 + 0.263x2 + 0.890. The findings underscore the significant impact of the college sports environment on students' participation in sports. Personal factors also play a crucial role in enhancing students' awareness and engagement in sports activities, whereas family factors have a minimal effect. Additionally, significant differences were observed in sports participation based on gender and educational level. To foster greater sports participation among college students, it is essential to strengthen curriculum development, provide teacher guidance, and improve the material and institutional environment.